Microgrid Electrode for Si Microwire Solar Cells with a Fill Factor of Over 80%. Issue 16 (26th August 2015) - Um, Han‐Don; Hwang, Inchan; Kim, Namwoo; Yu, Young J.; Wober, Munib; Kim, Ka‐Hyun; Seo, Kwanyong
Abstract : Here, a novel microgrid top electrode for highly efficient radial‐junction Si microwire solar cells is demonstrated. The microgrid electrode minimizes optical and electrical losses, thus ensuring proper function of the shallow (sheet resistance of ≈100 Ω sq −1 ) junction emitter. This leads to effective collection of the photocarriers from the shallow junction emitter through the top electrode without severe Auger/surface recombination, improving the overall power conversion efficiency of the Si microwire solar cell. With an optimized microgrid structure, 1 cm 2 microwire solar cells show a conversion efficiency of up to 16.5%, with an open‐circuit voltage of 565.2 mV and a short‐circuit current density of 35.9 mA·cm −2 ; this conversion efficiency is 72% higher than that of solar cells with an edge electrode (9.6%). Further, an ≈1 μm thick Ni electrode that is formed by electroplating considerably reduces the metal and contact resistances, which reproducibly yields a fill factor of over 80% (max 81.2%). Thus, the use of a novel microgrid to construct an ideal metal/emitter interface presents a unique opportunity to develop highly efficient microwire solar cells. Abstract : A novel top electrode using a microgrid structure to effectively collect photocarriers from the shallow junction emitter layer without optical and electrical losses is suggested. Though this initially only produces an fill factor of 75.1%, subsequent electroplating with a 1 μm thick nickel layer increases this to 81.2% and makes it possible to achieve a power conversion efficiency of 16.5%.